The influence of teacher–student relationship on Chinese high school students' academic motivation for the ideological and political subject: the mediating role of academic emotions - Wang, Yufeng; Jiang, Guohai; Yao, Zhendong; Liu, Lei (Frontiers in Psychology, 2024)
This study investigated the influence of teacher-student relationship on Chinese high students' academic motivation for the ideological and political subject and the parallel mediating roles of positive and negative academic emotions on this influence.The participants of this study were 425 Chinese high school students. This study measured teacher-student relationship, academic motivation, and academic emotions through several selfreported questionnaires. Structural equation models were used to analyze data and investigate the direct and indirect influence of teacher-student relationship on Chinese high school students' academic motivation for the ideological and political subject. Results: Teacher-student relationship had a significant, positive, and direct impact on Chinese high school students' academic motivation for the ideological and political subject. Moreover, positive and negative academic emotions, in parallel, mediated the relationship between these two factors. Discussion: This study demonstrates the important influence of teacher-student relationships on Chinese high school students' academic motivation for the ideological and political subject. A positive teacher-student relationship can directly increase students' academic motivation for this subject and indirectly enhance their motivation by generating positive academic emotions. Therefore, teachers should express care for their students, make friends with them, and be their partners in learning and life. Additionally, teachers need to pay close attention to students' academic emotions and provide them emotional support so that they can develop positive academic emotions while learning, and strive to establish and maintain a good teacher-student relationship.